The Elasticity of the U.S. Individual Income Tax: Its Calculation, Determinants and Behavior - Fries, Albert; Hutton, John P.; Lambert, Peter J. (The Review of Economics and Statistics, 1982)
Albert Fries, John P. Hutton, Peter J. Lambert, The Elasticity of the U.S. Individual Income Tax: Its Calculation, Determinants and Behavior, The Review of Economics and Statistics, Vol. 64, No. 1 (Feb., 1982), pp. 147-151